Xylophagous Millipede Surface Area to Volume Ratios are Size-dependent in Forests: A Brief Study - Mark Cooper (New Visions in Biological Science Vol. 8, 2022)
A consistent effect of increasing precipitation (and resource abundance) on body size reductions is known as a water conservation hypothesis. Here the objective was to investigate a water conservation hypothesis in millipedes and make a comparison between high long-term mean annual precipitation of forest (750-1500 mm) and lower long-term mean annual precipitation of savanna (544 mm) biome species (n=29, 6). When the confounding effects of phylogeny, sexual dimorphism, sexual size dimorphism, and size were controlled/removed, differences were found between six savanna species (Bicoxidens brincki, Doratogonus annulipes, Harpagophora spirobolina, Julomorpha hilaris, J. panda, Odontopyge tabulinus: 0,35975-2,632336 mm-1) and 29 forest species (Centrobolus: 0,000113-0,679931 mm-1; Sphaerotherium: 1,14271-3 mm-1) in the surface area: volume ratios. Savanna millipedes had size-independent surface area: volume ratios (0,519783 mm-1 in males and 0,823878 mm-1 in females). Differences occurred between size-independent savanna and size-dependent forest taxa in the surface area: volume ratios (t=3.75191, p=0.000013, n=58,12) controlling for the derivation whereby length/width increase affected surface area equally. Female savanna millipedes were longer than female forest millipedes (t=2.26165, p=0.016156, n=22, 6).